2019
DOI: 10.1177/0964663919869050
|View full text |Cite
|
Sign up to set email alerts
|

Problematising Symbolic Reparation: ‘Complex Political Victims’, ‘Dead Body Politics’ and the Right to Remember

Abstract: In light of the increasing importance of commemoration and memorialisation within the study of transitional justice, this article attempts to stimulate further critical discussion on the right to remember in societies transitioning out of prolonged conflict. Located within a wider exploration of the problematic overlap between the ‘politics of reparations’ and ‘dead body politics’ commonly found in transitioning societies, it argues that any prospective right to remember creates a tension between competing col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 66 publications
(67 reference statements)
0
7
0
2
Order By: Relevance
“…These various perspectives on the conflict have led to separate and competing hierarchies of victimhood emerging (Jankowitz, 2018), with those victims whose victimisation reaffirms and legitimates certain narratives being placed at the apex of the hierarchy, while those who expose ‘blind spots’ (Lawther, 2013: 164) in partisan narratives are positioned near the bottom. Hierarchical approaches to victimhood have suffused debate around which acts of violence should be subject to public inquiry and/or truth recovery (Rolston, 2020), which victimisers should face legacy case prosecutions for past violence (McGovern, 2019), which victims should be compensated for severe injury and/or bereavement (Jankowitz, 2018), and which victims should (not) be commemorated through public remembrance (Hearty, 2020). These debates are, of course, simply a corollary of more general failure to achieve consensus around who or what a ‘victim’ is in the NI context, with the inclusivist definition laid out in the Victims and Survivors (NI) Order 2006 being commended for recognising the complexity of victimhood during political conflict and criticised for equating ‘innocent victims’ with those who were killed or injured during the commission of political violence in equal measure (Jankowitz, 2018:11).…”
Section: Contesting August 1969mentioning
confidence: 99%
See 3 more Smart Citations
“…These various perspectives on the conflict have led to separate and competing hierarchies of victimhood emerging (Jankowitz, 2018), with those victims whose victimisation reaffirms and legitimates certain narratives being placed at the apex of the hierarchy, while those who expose ‘blind spots’ (Lawther, 2013: 164) in partisan narratives are positioned near the bottom. Hierarchical approaches to victimhood have suffused debate around which acts of violence should be subject to public inquiry and/or truth recovery (Rolston, 2020), which victimisers should face legacy case prosecutions for past violence (McGovern, 2019), which victims should be compensated for severe injury and/or bereavement (Jankowitz, 2018), and which victims should (not) be commemorated through public remembrance (Hearty, 2020). These debates are, of course, simply a corollary of more general failure to achieve consensus around who or what a ‘victim’ is in the NI context, with the inclusivist definition laid out in the Victims and Survivors (NI) Order 2006 being commended for recognising the complexity of victimhood during political conflict and criticised for equating ‘innocent victims’ with those who were killed or injured during the commission of political violence in equal measure (Jankowitz, 2018:11).…”
Section: Contesting August 1969mentioning
confidence: 99%
“…Empirical data sourced through online searches included local and national media coverage of anniversary events and commemorations; physical and non-physical memorialisation via murals, monuments, oral history accounts, and data bases; and official reports. As previous studies on victimhood and memorialisation have shown, whether critically examining what is said (or not) at commemorative events (Hearty, 2020) or what is inscribed (or not) on murals and monuments (Robinson, 2018; Rolston, 2020; Viggiani, 2014), the nexus between language choices, meaning making, and how victims are framed in accordance with post-conflict claims-making duly emerges.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…176 Memorialisation and commemoration of those who were killed during the conflict, also poses a serious source of contention where 'dead body politics' is played out to contest and reinforce selective interpretations of the past. 177 Such contestation and confrontation over the past may have a negative effect on a group in delegitimising their violence or may cement their position as drawing a line under the past of the armed struggle and their leaders distancing themselves from past violence as now being political generous. Such shifts are not dependent on former fighters, but also the State and civil society in allowing divergent narratives of the past and power structures to be legitimised in the aftermath of conflict.…”
Section: (Heading Level 2) Benefits and Costs Of Non-state Armed Groups Engagement In Reparationsmentioning
confidence: 99%